2013
DOI: 10.3141/2335-03
|View full text |Cite
|
Sign up to set email alerts
|

Improving Properties of Reclaimed Asphalt Pavement for Roadway Base Applications through Blending and Chemical Stabilization

Abstract: Finding innovative ways to incorporate reclaimed asphalt pavement (RAP) into highway base course applications will provide both environmental and economic benefits by allowing in situ recycling of material for projects such as widening or shoulder addition. RAP is a well-drained granular material; however, 100% RAP has low bearing strength and creeps under load. The objective of this research is to develop methods to improve RAP's strength while reducing creep to an acceptable level through blending with high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
14
0
3
Order By: Relevance
“…e percentage of RAP material in blends exceeds 20-25%, and the expected CBR value for the base course decreases as discussed by several authors [4][5][6][7][8][9][10][11][12]. Some researchers reported that the RAP content of the base mixtures should be limited to a maximum of 50% by weight [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…e percentage of RAP material in blends exceeds 20-25%, and the expected CBR value for the base course decreases as discussed by several authors [4][5][6][7][8][9][10][11][12]. Some researchers reported that the RAP content of the base mixtures should be limited to a maximum of 50% by weight [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For surface layers, West (2010) says that the average RAP incorporation rate in new asphalt mixes in the United States is between 12% and 15%, with a rate up to 30% resulting in the same performance as conventional mixtures that only use virgin aggregates. Other authors, as Rahman et al (2014), have obtained good results studying permanent deformation in the Hamburg Wheel Tracking Device with RAP percentages of up to 50%, surpassing some of the results of mixes with rates of 10% and 30%.…”
Section: Recycled Layersmentioning
confidence: 99%
“…The combination of RAP and different proportions of crushed limerock was studied by Bleakley and Cosentino (2012) with the objective of increasing the resistance and bearing capacity of the recycled mix, to be used as a base layer. It was observed that higher proportions of crushed limerock resulted in smaller deformations and higher stiffness.…”
Section: Inputs Used In Recycling With Foamed Bitumenmentioning
confidence: 99%
See 2 more Smart Citations